Aplicación del método SPH al estudio hidráulico de estructuras. Análisis hidrodinámico del aliviadero en pozo de la presa de Nagore (Navarra). Issue 1 (1st January 2016) - López, D.; Díaz, R.; Rebollo, J.J.; Ramos, T.; Andrés, F.R.; Berga, M.I.
Abstract: Many calibration works have been performed to support the validity of the smoothed particle hydrodynamics (SPH) method for studying turbulent-free surface flows. However, its high computational requirements made it difficult to use in real cases. The development of techniques for supercomputing graphics processing units (GPU) has changed this situation, and is allowing its use as a design tool. CEDEX has developed a model based on this technology, SPHERIMENTAL, in order to support studies on physical modelling. This has enabled the model to be calibrated in order to study complex phenomena. This paper shows the works done to check the hydrodynamics free surface flows in the Nagore dam morning glory spillway, describing both the previous calibration works and the results obtained.